Governing, protecting, and regulating the future of genome editing : the significance of ELSPI perspectives - Slokenberga, Santa, 1987-; Minssen, Timo; Nordberg, Ana (Brill/Nijhoff, 2023)
"This edited collection examines the ethical, legal, social and policy implications of genome editing technologies. Moreover, it offers a broad spectrum of timely legal analysis related to bringing genome editing to the market and making it available to patients, including addressing genome editing technology regulation through procedures for regulatory approval, patent law and competition law. In twelve chapters, this volume offers persuasive arguments for justifying transformative regulatory interventions regarding human genome editing, as well as the various legal venues for introducing necessary or desirable changes needed to create an environment for realizing the potential of genome editing technology for the benefit of patients and society"-- Provided by publisher.
"Originally published, in part, as Volume 29, Issue 3-5 (2022) of Brill's journal European journal of health law."
Keywords: Gene therapy -- Law and legislation.; Genetic engineering -- Law and legislation.; Human genetics -- Law and legislation.; Gene editing -- Technological innovations.; Biotechnology -- Patents.; Édition génique -- Innovations.; Biotechnologie -- Brevets d'invention.; Biotechnology; Gene therapy -- Law and legislation; Genetic engineering -- Law and legislation; Human genetics -- Law and legislation; Patents